Colossians and Philemon : a handbook on the Greek text - Campbell, Constantine R. (2013)
"Analysis of the Greek text of Colossians and Philemon"--
Introduction -- Colossians 1:1-2 -- Colossians 1:3-8 -- Colossians 1:9-14 -- Colossians 1:15-20 -- Colossians 1:21-23 -- Colossians 1:24-29 -- Colossians 2:1-5 -- Colossians 2:6-15 -- Colossians 2:16-19 -- Colossians 2:20-23 -- Colossians 3:1-4 -- Colossians 3:5-11 -- Colossians 3:12-17 -- Colossians 3:18-4:1 -- Colossians 4:2-6 -- Colossians 4:7-9 -- Colossians 4:10-14 -- Colossians 4:15-18 -- Philemon 1-3 -- Philemon 4-7 -- Philemon 8-16 -- Philemon 17-22 -- Philemon 23-25.
Includes bibliographical references (p. 101-106) and indexes.
Keywords: Bible. -- Criticism, Textual; Bible. -- Versions; Bible. -- Criticism, Textual; Bible. -- Versions